Search for the production of four top quarks in the single-lepton and opposite-sign dilepton final states in proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Dragicevic, M.; Eroe, J.; Del Valle, A. Escalante; Flechl, M.; Fruehwirth, R.; et al. (Springer Science and Business Media LLC, 2019)
Abstract A search for the standard model production of four top quarks (pp → $$ \mathrm{t}\overline{\mathrm{t}}\mathrm{t}\overline{\mathrm{t}} $$ t t ¯ t t ¯ ) is reported using single-lepton plus jets and opposite-sign dilepton plus jets signatures. Proton-proton collisions are recorded with the CMS detector at the LHC at a center-of-mass energy of 13 TeV in a sample corresponding to an integrated luminosity of 35.8 fb−1. A multivariate analysis exploiting global event and jet properties is used to discriminate $$ \mathrm{t}\overline{\mathrm{t}}\mathrm{t}\overline{\mathrm{t}} $$ t t ¯ t t ¯ from $$ \mathrm{t}\overline{\mathrm{t}} $$ t t ¯ production. No significant deviation is observed from the predicted background. An upper limit is set on the cross section for $$ \mathrm{t}\overline{\mathrm{t}}\mathrm{t}\overline{\mathrm{t}} $$ t t ¯ t t ¯ production in the standard model of 48 fb at 95% confidence level. When combined with a previous measurement by the CMS experiment from an analysis of other final states, the observed signal significance is 1.4 standard deviations, and the combined cross section measurement is $$ {13}_{-9}^{+11} $$ 13 − 9 + 11 fb. The result is also interpreted in the framework of effective field theory.
Keywords: GeV-cms; top physics; Nuclear and Plasma Physics (for-2020); QC770-798; Atomic; channel cross section: upper limit; Mathematical Sciences; B physics; Physics, Particles & Fields; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); Particle and Plasma Physics; effective field theory; Mathematical physics (for-2020); Hadron-Hadron scattering (experiments); [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; Particle Physics Experiments; Particle and high energy physics (for-2020); Top physic; info:eu-repo/classification/ddc/530; Mathematical Physics; Particle and High Energy Physics (for-2020); Exotica; Quantum Physics; Mathematical Physics; CMS; Physics; dilepton: final state; Physical Sciences (for-2020); Q007d13; ddc:530; Particle and High Energy Physics; Quantum Physics (for); Higgs physics; Top Physics; Nuclear and Plasma Physics; Physics, LHC, CMS, Top quark; Nuclear & Particles Physics; Hadron-Hadron Scattering (Experiments); CERN LHC Coll; Top physics; Photon production; Physical Sciences; Atomic, Molecular, Nuclear, Particle and Plasma Physics; jet: signature; Physique des particules élémentaires; Mathematical Physics (for-2020); Mathematical Sciences (for-2020); Particle physics; top: multiple production; LHC; High energy physics; Experimental particle physics; LHC; CMS; Particle Physics Experiments; Hadron-Hadron scattering (experiments); Supersymmetry; Higgs physics; Beyond Standard Model; Photon production; Elementary Particles and Fields; B physics; Exotica; Long-lived particles; Top physics; Hadron-Hadron scattering (experiments); Top physics; High Energy Physics - Experiment; High Energy Physics - Experiment; data analysis method; p p: scattering; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; Pair production; Particles & Fields; Particle and Plasma Physics (for); FOS: Physical sciences; final state: ((n)jet lepton); Nuclear and plasma physics (for-2020); statistical analysis; Nuclear and particle physics. Atomic energy. Radioactivity; Mathematical Physics (for); Nuclear; High energy physics; Hadron-Hadron scattering (experiments); Top physics; ЭБ БГУ::ЕСТЕСТВЕННЫЕ И ТОЧНЫЕ НАУКИ::Физика; Quantum Physics; Science & Technology; Particle physics; Large hadron collider; CMS; hep-ex; background; final state: ((n)jet dilepton); Molecular; Nuclear & Particles Physics (science-metrix); Física; Hadron-Hadron scattering (experiments); Top physics